Les révolutions du commerce. France, xviiie-xxie siècle - Daumas, Jean-Claude (Les Cahiers de la MSHE Ledoux, 2020)
Since the end of the 18th century, there have always been shopkeepers to experiment with new ways of meeting consumer demand. It is this story that this book retraces for France, from the "magasin de nouveautés" to e-commerce, including the department store and the hypermarket. The analysis focuses on both retail innovations and business revolutions by disentangling the interactions between business transformations and consumer developments. This approach puts into perspective the current distribution crisis, which is concentrated in the difficulties of the hypermarket and questions the ability of distributors to reinvent it.